Sleep Quality and Junk Food Consumption in Relation to Body Mass Index Among Medical Students at Universitas Muhammadiyah Yogyakarta - Muhammad Pramono; Zulkhah Noor (Indonesian Journal Publisher, 2026)
This study sought to investigate the correlation between sleep quality and the frequency of junk food consumption with body mass index (BMI) among medical students at Universitas Muhammadiyah Yogyakarta (UMY). A quantitative cross-sectional study was executed via purposive sampling of medical students from the 2020–2022 cohorts. An online questionnaire was used to collect data on the respondents' characteristics, their self-reported weight and height (to calculate BMI), their sleep quality (using the Pittsburgh Sleep Quality Index), and how often they ate junk food (using a food frequency questionnaire). Separate correlation studies were conducted for men and women. There was no significant link between sleep quality and BMI in either males (p=0.502) or women (p=0.118). The frequency of junk food consumption did not show a significant correlation with BMI in women (p=0.292). For men, the frequency of junk food consumption had a strong positive link with BMI (r=0.490, p=0.008). In conclusion, sleep quality did not connect with BMI in either gender; nevertheless, increased junk food consumption was linked to a higher BMI exclusively among male students.